2015
DOI: 10.1101/033514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reticulate evolution is favored in influenza niche switching

Abstract: 12Reticulate evolution is thought to accelerate the process of evolution beyond simple genetic drift 13 and selection, helping to rapidly generate novel hybrids with combinations of adaptive traits. 14 However, the long-standing dogma that reticulate evolutionary processes are likewise 15 advantageous for switching ecological niches, as in microbial pathogen host switch events, has 16 not been explicitly tested. We use data from the influenza genome sequencing project and a 17 phylogenetic heuristic approach t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Reassortment of IAV gene segments encoding HA surface glycoproteins is a mechanism for jumping between taxonomically distinct hosts (Ma, Hill, Zabilansky, Yuan, & Runstadler, 2016) and has been implicated in the emergence of pandemic influenza viruses in humans (Ward, Lycett, Avila, Bollback, & Leigh Brown, 2013). Though no reassortment between low pathogenic and HPAI HA subtypes was detected in Iceland during our eight-year sampling timeframe, we detected strong support for reassortment between gull-associated H16 to H2 in our sample (Figure 5).…”
Section: Discussionmentioning
confidence: 57%
“…Reassortment of IAV gene segments encoding HA surface glycoproteins is a mechanism for jumping between taxonomically distinct hosts (Ma, Hill, Zabilansky, Yuan, & Runstadler, 2016) and has been implicated in the emergence of pandemic influenza viruses in humans (Ward, Lycett, Avila, Bollback, & Leigh Brown, 2013). Though no reassortment between low pathogenic and HPAI HA subtypes was detected in Iceland during our eight-year sampling timeframe, we detected strong support for reassortment between gull-associated H16 to H2 in our sample (Figure 5).…”
Section: Discussionmentioning
confidence: 57%
“…Other factors such as vector distribution and habitats are under study and will be reported separately. Virus phylogenies are thoroughly established tools to analyze transmission patterns and to estimate the origin of incursions for a wide variety of viruses, including influenza A, chikungunya, foot-and-mouth disease virus, and hepatitis C virus (Brito et al 2017;Lamoury et al 2015;Ma et al 2016;Volk et al 2010). Our whole-genome VSV phylogenetic analysis allowed for the grouping of virus sublineages into temporally and geographically distinct patristic groups, which in turn enabled us to confirm VS overwintering as an epidemiological mechanism and to compare individual PGs to seasonally varying environmental conditions.…”
Section: Discussionmentioning
confidence: 99%